2002
DOI: 10.1111/j.1439-0485.2002.tb00035.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of a Macroalgal Covering Event on the Microphytobenthos Community in Intertidal Sediment (Marano Lagoon, Northern Adriatic Sea)

Abstract: This study examines the variation in microphytobenthos structure and functioning in an intertidal lagoon during a macroalgal covering event. Multivariate techniques, applied on the recorded data, highlighted a clear seasonal pattern except for the July sample. The sudden macroalgae (Cladophora sp.) development, which occurred in that month, enabled us to identify the massive covering as a disturbance factor on the benthic ecosystem. This biotic anomaly affected benthic microalgal production and community respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(51 reference statements)
2
6
0
Order By: Relevance
“…Consequently, the lower value of salinity recorded in the inner station of Marano is probably due to both the ebb-tide and the larger supply of freshwater (Fonda Umani & Specchi, 1982). The microphytobenthic ABU found in this study appeared comparable with those reported by Sdrigotti & Welker (2002) for the Marano lagoon and by Blasutto et al (2003) for subtidal sediments of shallow coastal waters in the Gulf of Trieste. Our ABU was lower than that found by Facca & Sfriso (2002) in the central part of the Venice Lagoon.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consequently, the lower value of salinity recorded in the inner station of Marano is probably due to both the ebb-tide and the larger supply of freshwater (Fonda Umani & Specchi, 1982). The microphytobenthic ABU found in this study appeared comparable with those reported by Sdrigotti & Welker (2002) for the Marano lagoon and by Blasutto et al (2003) for subtidal sediments of shallow coastal waters in the Gulf of Trieste. Our ABU was lower than that found by Facca & Sfriso (2002) in the central part of the Venice Lagoon.…”
Section: Discussionsupporting
confidence: 93%
“…Gross primary production rates reported in this study are the first determined with the 14 C-tracer method in an intertidal lagoon ecosystem in the Northern Adriatic Sea. These PP values are significantly lower than those estimated with oxygen measurements in the Marano lagoon (Sdrigotti & Welker, 2002). Nevertheless, the rates we obtained are comparable with those estimated with oxygen method in a non-tidal sandy beach of the Gulf of Gdansk (southern Baltic) (Urban-Malinga & Wiktor, 2003).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…They focused mainly on recent mercury contamination in the bottom sediments (Piani et al 2005, Covelli et al 2009). Biological studies have encompassed the distribution of picoplanktonic cyanobacteria (Paoli et al 2007), phytoplankton (Facca & Sfriso 2009), microphytobenthos (MPB) (Sdrigotti & Welker 2002, Blasutto et al 2005) and macroalgae (Falace et al 2009). Higher heterotrophic levels have also been considered (Sconfietti & Marchini 2001, Dondi et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…An inverse relation between photosynthetic efficiency and salinity at a lagoonal system in the Northern Adriatic coast has been reported by Blasutto et al (2005), and Barranguet (1997) showed the same relation associated to the high light intensity, both influencing the environmental production. In response to these abiotic parameters, microphytobenthic communities had to adapt to a series of stress factors migrating to deeper layers of sediment and consequently reducing photosynthesis rate and oxygen production at the sediment surface layer (Barranguet et al 1998;Sdrigotti and Welker 2002;Brotas et al 2003).…”
Section: Discussionmentioning
confidence: 99%